2012
DOI: 10.1097/ccm.0b013e3182514be9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of selective inhibition of renal inducible nitric oxide synthase on renal blood flow and function in experimental hyperdynamic sepsis*

Abstract: In hyperdynamic sepsis, intrarenal infusion of a highly selective inducible nitric oxide synthase inhibitor did not reduce the elevated renal blood flow or improve renal function. In contrast, renal blood flow was reduced by infusion of a nonselective NOS inhibitor or a high dose of a partially selective inducible nitric oxide synthase inhibitor. The renal vasodilatation in septic acute kidney injury may be due to nitric oxide derived from the endothelial and neural isoforms of nitric oxide synthase, but their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 35 publications
2
28
0
1
Order By: Relevance
“…However, it is unlikely that the effect of TLR4 inhibition on renal function in this study is mediated by reduced NO formation as there were no differences in either MAP or renal blood flow and as TAK-242 did not affect NOx or cyclic guanosine monophosphate (cGMP) levels. This view is supported by results demonstrating no effect on renal function after intrarenal NO synthase inhibition during Gramnegative sepsis [33].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…However, it is unlikely that the effect of TLR4 inhibition on renal function in this study is mediated by reduced NO formation as there were no differences in either MAP or renal blood flow and as TAK-242 did not affect NOx or cyclic guanosine monophosphate (cGMP) levels. This view is supported by results demonstrating no effect on renal function after intrarenal NO synthase inhibition during Gramnegative sepsis [33].…”
Section: Discussionsupporting
confidence: 76%
“…A recently promoted hypothesis for sepsis-induced AKI is that the inflammatory response causes a preferential dilatation of renal efferent arterioles, increasing renal blood flow but reducing the hydrostatic pressure for glomerular filtration and thereby glomerular filtration rate (GFR) [32]. The most important vasodilator released in sepsis is NO, and it has been suggested that excessive intra-renal NO could be responsible for the reduction in postglomerular resistance [33]. However, it is unlikely that the effect of TLR4 inhibition on renal function in this study is mediated by reduced NO formation as there were no differences in either MAP or renal blood flow and as TAK-242 did not affect NOx or cyclic guanosine monophosphate (cGMP) levels.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some pathophysiological processes may be associated with increased global renal blood flow [9,10] despite loss of function. In such instances, there is experimental evidence that, at least in sepsis, this phenomenon may be caused by intra-renal shunting [11].…”
Section: Introductionmentioning
confidence: 99%
“…Finally it should be noted that in the sepsis induced mitochondrial dysfunction there is an increased production of nitric oxide, secondary to the induced form of the type II nitric oxide synthase [becoming another therapeutic target], and inhibiting the Neural isoform [NOS] so far with arguable results [50,51].…”
Section: Treating the Hypoperfusionmentioning
confidence: 99%